DYNAMIC CAPABILITIES EROSION IN INDONESIA’S RETAIL INDUSTRY: CONSUMERS’ PERSPECTIVE ON MATAHARI DEPARTMENT STORE - Riveria Sari; Ferri Woejaya; Teofilus Teofilus (Primanomics : Jurnal Ekonomi & Bisnis, 2020)
This research was conducted to analyze the effect of dynamic capabilities erosion on firm’s survival according to consumers’ perspective, using sensing erosion, seizing erosion, and reconfiguring erosion as the independent variables (X) and firm survival as the dependent variable (Y). This research uses quantitative research methods with data processing using SPSS. Data collection was carried out by distributing questionnaires online through Google form to 500 student respondents who had visited Matahari Department Store in Indonesia. Sampling is done by purposive sampling technique. The questionnaires that qualify to be analyzed are 158 questionnaires. The result of data processing shows that the effect of the independent variable on the dependent variable is 40.3%. The results of this study is according to consumers’ perspective, sensing erosion, seizing erosion, and reconfiguring erosion affect firm survival.